Studi Perhitungan Indeks Keandalan Sistem Tenaga Listrik Menggunakan Graphical User Interface Matlab pada PT PLN (Persero) Rayon Kota Pinang - Adri Senen; Titi Ratnasari; Dwi Anggaini (Sekolah Tinggi Teknik PLN, 2019)
The level of reliability of a distribution system is very important to ensure the continuity of electricity supply to consumers. This research was conducted to calculate the Saidi reliability index and the Saifi 20 kV distribution system in Pinang PLN in 2017 with the help of the Matlab R2008a application. A GUI is one of the Matlab programs that is widely used in describing information and commands, and its users are possible to form and format themselves according to the needs of the system itself. With the help of this software, it is hoped that it will be easier to calculate the system reliability index, namely the calculation of SAIDI and SAIFI, then the results can be made so that the database is more organized. The calculation results obtained will show the highest and lowest SAIDI and SAIFI values ​​that occur in each of the current months, making it easier to evaluate, analyze and improve the reliability of the electrical power system network in the future, especially in PT.